INSTITUTIONAL CAPACITY OF LOCAL GOVERNMENT - Lopushynskyi, Ivan; Krasii, Mariia (Public Management and Policy, 2025)
The article focuses on the institutional capacity of a local government as a key prerequisite for the effective implementation of powers during the decentralization and reform of public administration in Ukraine. The purpose of this study is to theoretically substantiate the institutional capacity of local government, clarify its essence through the lens of the institutional approach, and systematize the main components that determine the local government's ability to ensure an appropriate level of management and provide public services. The relevance of the study is due to the lack of a unified approach to the definition and assessment of institutional capacity, as well as the need to integrate theoretical developments and the practical needs of territorial communities. As a result of the analysis of scientific sources, regulatory legal acts of Ukraine and documents of international organizations, the feasibility of considering local government as a full-fledged institution of public power is substantiated. The content of the concept of “institutional capacity” is clarified as the ability of an institution to stably and effectively perform its assigned functions on the basis of proper legal regulation, effective organizational structure, professional staffing, financial self-sufficiency and developed communication mechanisms. Five key components of the institutional capacity of local government bodies are identified: personnel, organizational and managerial, financial, regulatory and legal and communication and informational. Their content, functional significance and interrelationship are revealed, which allows for a comprehensive assessment of the level of capacity of local government bodies in modern conditions. It is concluded that the institutional capacity of local government bodies is a multidimensional and integrated characteristic, on which the effectiveness of local government, the quality of public services and the level of trust of citizens directly depend. Its formation and strengthening are possible only under the condition of systematic development of all components, coordinated with the constitutional principles of local self-government, national legislation and standards of the European Charter of Local Self-Government. It is substantiated that a comprehensive approach to assessing institutional capacity creates a basis for improving management practices, implementing the principle of subsidiarity and ensuring sustainable development of territorial communities.